Targeting microglia attenuates neuroinflammation‐related neural damage in mice carrying human PLP1 mutations. Issue 2 (22nd November 2018) - Groh, Janos; Klein, Dennis; Berve, Kristina; West, Brian L.; Martini, Rudolf
Abstract: Genetically caused neurological disorders of the central nervous system (CNS) usually result in poor or even fatal clinical outcome and few or no causative treatments are available. Often, these disorders are associated with disease‐amplifying neuroinflammation, a feature shared by progressive forms of multiple sclerosis (PMS), another poorly treatable disorder of the CNS. We have previously generated two mouse lines carrying distinct mutations in the oligodendrocytic PLP1 gene that have initially been identified in patients fulfilling clinical criteria for multiple sclerosis (MS). These mutations cause a loss of function of the gene product resulting in a histopathological and clinical phenotype common to both PMS and genetic CNS disorders, like hereditary spastic paraplegias. Importantly, neuroinflammation comprising adaptive immune reactions promotes disease progression in these PLP1 mutant models, opening the possibility to improve disease outcome of the respective disorders by targeting/modulating inflammation. We here show that PLX3397, a potent inhibitor of the CSF‐1R and targeting innate immune cells, attenuates neuroinflammation in our models by reducing numbers of resident microglia and attenuating T‐lymphocyte recruitment in the CNS. This leads to an amelioration of demyelination, axonopathic features and neuron loss in the retinotectal system, also reflected by reduced thinning of the inner retinal composite layer in longitudinal studies using noninvasive optical coherence tomography. Our findings identify microglia as important promoters of neuroinflammation‐related neural damage and CSF‐1R inhibition as a possible therapeutic strategy not only for PMS but also for inflammation‐related genetic diseases of the nervous system for which causal treatment options are presently lacking. Main Points: Treatment of PLPmut mice with PLX3397 depletes microglia of the CNS, reduces neuroinflammation by Tlymphocytes, and attenuates axon and myelin degeneration, neuron loss and retinal thinning.